Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

gocho

  • 3 years ago

Solve for x. 3x − 1 = -10

  • This Question is Closed
  1. iAmCool
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Simplifying 3x + -1 = -10 Reorder the terms: -1 + 3x = -10 Solving -1 + 3x = -10 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3x = -10 + 1 Combine like terms: -1 + 1 = 0 0 + 3x = -10 + 1 3x = -10 + 1 Combine like terms: -10 + 1 = -9 3x = -9 Divide each side by '3'. x = -3 Simplifying x = -3

  2. blakevarndell
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    |dw:1355182095624:dw|

  3. iAmCool
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Yours was good too. c:

  4. blakevarndell
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    :P

  5. iAmCool
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    Aha, help me with my question? http://openstudy.com/study#/updates/50c66f31e4b0b766106d9a87

  6. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy